Impact of T cell ratios on survival in pleural mesothelioma: insights from tumor microenvironment analysis - Klotz, Laura Valentina; Weigert, Andreas; Eichhorn, Florian; Allgäuer, Michael; Muley, Thomas; Shah, Rajiv; Savai, Rajkumar; Eichhorn, Martin E.; Winter, Hauke (Cancers, 2024)
Background: Immunotherapy has significantly improved overall survival in patients with pleural mesothelioma, yet this benefit does not extend to those with the epithelioid subtype. Tumor growth is believed to be influenced by the immune response. This study aimed to analyze the tumor microenvironment to gain a better understanding of its influence on tumor growth. Methods: The tumor immune cell infiltration of 188 patients with pleural mesothelioma was characterized by multiplex immunofluorescence staining for CD3+ cells (CD3+), CD4+ cells (CD3+/CD4+), CD8+ cells (CD3+/CD8+), Treg (CD3+/CD4+/CD8-/CD163-/Foxp3+), PD1 cells (PD1+), and T helper cells (CD3+/CD4+/CD8-/CD163-/FoxP3-). The distribution of specific immune cells was correlated with clinical parameters. Results: A total of 188 patients with pleural mesothelioma (135 epithelioid, 9 sarcomatoid, 44 biphasic subtypes) were analyzed. The median age was 64.8 years. Overall survival was significantly longer in the epithelioid subtype than in the non-epithelioid subtype (p = 0.016). The presence of PD-L1 expression had a negative effect on overall survival (p = 0.041). A high ratio of CD4+ cells to regulatory T cells was associated with a significantly longer overall survival of more than 12 months (p = 0.015). The ratio of CD4+ cells to regulatory T cells retained its significant effect on overall survival in the multivariate analysis. Conclusions: Distinct differences in the T cell immune infiltrates in mesothelioma are strongly associated with overall survival. The tumor microenvironment could therefore serve as a source of prognostic biomarkers.
Gesehen am 03.04.2025